2008
DOI: 10.1590/s0074-02762008000100006
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of co-association of C-reactive protein and nitric oxide in malaria in endemic areas of Iran

Abstract: In addition to numerous immune factors, C-reactive protein (CRP) and nitric oxide (NO) are believed to be molecules of malaria immunopathology. The objective of this study was to detect CRP and NO inductions by agglutination latex test and Griess microassay respectively in both control and malaria groups from endemic areas of Iran, including Southeastern (SE) (Sistan & Balouchestan, Hormozgan, Kerman) and Northwestern (NW) Key words: C-reactive protein -Iran -nitric oxide -malaria -Plasmodium Malaria is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Still considering malaria, weaker NO production by macrophages was associated with a worst outcome of cerebral malaria (Gramaglia et al 2006;Lopansri et al 2003), indicating that NO is essential in parasite killing, confirming previous reports (Balmer et al 2000;Nahrevanian 2006;Nahrevanian et al 2008). However, excessive amounts of NO and peroxynitrite can aggravate infections, explaining why NO overload could also be toxic, especially to the brain (Ferrari et al 2009;Nahrevanian 2006;Nahrevanian et al 2008). In fact, NO decreases expression of intercellular and vascular cell adhesion molecules inhibiting P. falciparum adhesion to endothelium of brain vessels, but the parasite induces release of IgE and subsequent NO overload which aggravates cerebral malaria (Mazie and Idrissa-Boubou 1999).…”
Section: No Killing By Phagocytes In Candida and Malaria: When The Exsupporting
confidence: 84%
See 1 more Smart Citation
“…Still considering malaria, weaker NO production by macrophages was associated with a worst outcome of cerebral malaria (Gramaglia et al 2006;Lopansri et al 2003), indicating that NO is essential in parasite killing, confirming previous reports (Balmer et al 2000;Nahrevanian 2006;Nahrevanian et al 2008). However, excessive amounts of NO and peroxynitrite can aggravate infections, explaining why NO overload could also be toxic, especially to the brain (Ferrari et al 2009;Nahrevanian 2006;Nahrevanian et al 2008). In fact, NO decreases expression of intercellular and vascular cell adhesion molecules inhibiting P. falciparum adhesion to endothelium of brain vessels, but the parasite induces release of IgE and subsequent NO overload which aggravates cerebral malaria (Mazie and Idrissa-Boubou 1999).…”
Section: No Killing By Phagocytes In Candida and Malaria: When The Exsupporting
confidence: 84%
“…Lacking of NO synthesis from leucocyte phagocytes is associated with increased risk of infection by Porphyromonas gingivalis (Gyurko et al 2003), Trypanosoma cruzi (Hölscher et al 1998;Talvani et al 2002), and P. falciparum (Boutlis et al 2003). Still considering malaria, weaker NO production by macrophages was associated with a worst outcome of cerebral malaria (Gramaglia et al 2006;Lopansri et al 2003), indicating that NO is essential in parasite killing, confirming previous reports (Balmer et al 2000;Nahrevanian 2006;Nahrevanian et al 2008). However, excessive amounts of NO and peroxynitrite can aggravate infections, explaining why NO overload could also be toxic, especially to the brain (Ferrari et al 2009;Nahrevanian 2006;Nahrevanian et al 2008).…”
Section: No Killing By Phagocytes In Candida and Malaria: When The Exsupporting
confidence: 73%
“…It is suggested that the detrimental effect of NOS is related to the L-arginine and NO concentrations, because NO at high concentration has a clear anti-inflammatory effect [139][140][141][142]. Thus, activation of NO could be a potential therapeutic strategy to suppress parasitic infections [143][144][145]. Nevertheless, the functional role of NO and NOS isoforms in the immune responses of host against the majority of parasites is still highly controversial.…”
Section: Conclusive Remarksmentioning
confidence: 99%
“…As L-Arg has long been identified as an essential amino acid for Leishmania growth, promastigotes could not be maintained in L-Arg-free media (Krassner and Flory, 1971), suggesting mechanisms of L-Arg uptake and utilization in Leishmania parasites (Shaked-Mishan et al, 2006). This study is a continuous research of authors previous publications (Nahrevanian, 2004(Nahrevanian, , 2006Nahrevanian and Amini, 2009;Nahrevanian et al, 2006Nahrevanian et al, , 2008Nahrevanian et al, , 2009a2009b). Therefore, the aim of this study is to investigate the partial immunotherapy of leishmaniasis by in vivo trial of L-Arg in Balb/c mice infected with Leishmania major via nitric oxide pathway.…”
Section: Introductionmentioning
confidence: 81%